An efficient multiscale numerical simulation method for immersion heat dissipation in porous media. (August 2022) - Meng, Like; Wu, Wei; Wang, Shuangfeng
Abstract: In this paper, a multi-scale numerical simulation method is proposed by the layered method for immersion heat dissipation of high heat flux electronic cooling. The mathematical model of a tetrakaidecahedron is used to simplify structure of the porous medium. The geometry of it constructed by the spin-stacking approach is much closer to realistic single-layer or thin porous materials. The Lattice Boltzmann method (LBM) is used to simulate the boiling process by the modification code of palabos. Macroscopic level of temperature and flow field is obtained by COMSOL. It is verified that the multi-scale numerical simulation method is efficient and easy to deliver in simulation of porous medium at large extent. It has little error (less than 5%) compared with experimental results. Compared with WP model, it can save computing resources (up to 70%).